Four-Dimensional (4D) Printing: A New Evolution in Computed Tomography-Guided Stereolithographic Modeling. Principles and Application - Chae, Michael P.; Hunter-Smith, David J.; De-Silva, Inoka; Tham, Stephen; Spychal, Robert T.; Rozen, Warren Matthew (Journal of Reconstructive Microsurgery, 2015)
Background Over the last decade, image-guided production of three-dimensional (3D) haptic biomodels, or rapid prototyping (RP), has transformed the way surgeons conduct preoperative planning. In contrast to earlier RP techniques such as stereolithography, 3D printing has introduced fast, affordable office-based manufacturing. We introduce the concept of 4D printing for the first time by introducing time as the fourth dimension to 3D printing.Methods The bones of the thumb ray are 3D printed during various movements to demonstrate four-dimensional (4D) printing. Principles and validation studies are presented here.Results 4D computed tomography was performed using “single volume acquisition” technology to reduce the exposure to radiation. Three representative scans of each thumb movement (i.e., abduction, opposition, and key pinch) were selected and then models were fabricated using a 3D printer. For validation, the angle between the first and the second metacarpals from the 4D imaging data and the 4D-printed model was recorded and compared.Conclusion We demonstrate how 4D printing accurately depicts the transition in the position of metacarpals during thumb movement. With a fourth dimension of time, 4D printing delivers complex spatiotemporal anatomical details effortlessly and may substantially improve preoperative planning.
Keywords: 3D printing; reconstructive surgery; template; 4D; 3D model; dimensional